Correlation and Influencing Factors Between Laryngopharyngeal Reflux Disease and Sleep Status in Patients - Liu, Yue; Wu, Jian; Xiao, Feng; Gu, Xiaofeng; Ji, Li (Frontiers in Surgery, 2022)
To observe the correlation between laryngopharyngeal reflux disease (LPRD) and sleep status of patients, and to explore the related factors of LPRD. 416 patients who visited the otorhinolaryngology clinic in our hospital from June 2019 to June 2021 were selected as the research subjects. The subjects were divided into a patients group (120 patients) with an the reflux symptom index (RSI)>13 and a control group (296 patients) with an RSI≤13 according to the RSI scale score. General patient information was collected. Assess the sleep status and emotional status of patients in the two groups, as well as the related influencing factors for the onset of LPRD. The correlation between sleep status and depressive mood in LPRD patients was analyzed. Results: Sleep disorder may lead to the occurrence or aggravation of anxiety and depression in patients with LPRD, and it is an independent risk factor for the development of LPRD. Clinical attention to the treatment of sleep disorders in patients with LPRD may be conducive to improving the efficacy of LPRD.